Anti-p200 pemphigoid responding to dapsone - Laura Van Lerberghe; Audrey Lasek; Pierre Gosset; Fabienne Jouen; Philippe Modiano (Wolters Kluwer Medknow Publications, 2014)
Anti-p200 pemphigoid is a rare autoimmune subepidermal blistering disease. Clinical presentation is similar to standard bullous pemphigoid (BP) but mucous membranes and cephalic lesions are more frequent. Histology and direct immunofluorescence (IF) are identical to BP but indirect IF discloses linear deposits of immunoglobulin G (IgG) on the dermal side of artificial salt-split skin. Specific diagnosis is based on western immunoblotting that shows circulating IgG recognizing a 200-kDa protein localized on the dermal extract. The 200-kDa antigen was recently identified as laminin γ1. Anti-p200 pemphigoid should be considered before all atypical or topical steroid-resistant bullous disease, as well as mucous membranes pemphigoid or epidermolysis bullosa acquisita. Dapsone appears to be the most effective treatment and should be used as the first option in combination with topical steroids. In this report, we describe the case of a patient with a typical clinical and immunopathological anti-p200 pemphigoid, responding to a combination of topical steroids and dapsone.